V-like structure in the correlated electron momentum distribution for nonsequential double ionization of helium - Truong , Dang Hoai Thu; Huynh , Van Son; Pham , Nguyen Thanh Vinh (Tạp chí Khoa học Trường Đại học Sư phạm Thành phố Hồ Chí Minh, 2019)
We investigate the nonsequential double ionization process of He atom by using classical three-dimensional ensemble model. The result shows that a pronounced V-like structure is exhibited in the two-electron momentum distribution along the laser polarization axis. At high laser intensity, this structure which was observed experimentally [Phys. Rev. Lett. 99, 263003 (2007)] can be explained by the asymmetric energy sharing of two electrons at recollision process.